Intraoperative Methadone for the Prevention of Postoperative Pain: A Randomized, Double-blinded Clinical Trial in Cardiac Surgical Patients. Issue 4 (August 2016) - Murphy, Glenn S.; Szokol, Joseph W.; Avram, Michael J.; Greenberg, Steven B.; Marymont, Jesse H.; Shear, Torin; Parikh, Kruti N.; Patel, Shivani S.; Gupta, Dhanesh K.
Abstract : (Abstracted from Anesthesiology, 122:1112–1122, 2015) There is a high prevalence of acute postoperative pain in cardiac surgical patients, especially during the first 2 days after surgery. Indeed, most patients have reported moderate to severe pain during intensive care unit (ICU) admission, even with treatment with potent opioids.